G194 Vitamin d and vitamin d deficiency: how much do parents know?. (27th April 2015) - Carr, R; Mahmood, D; McEvoy, A
Abstract : Background: Vitamin D deficiency is prevalent among children and the majority are unaware of their low vitamin D levels. Vitamin D is an important component for the optimal health of children, as well as playing a role in reducing the risk of various chronic health issues in the future. This study aimed to gauge the level of awareness and knowledge of vitamin D amongst the parents of paediatric orthopaedic patients. Study design: A retrospective observational study was conducted using a paper-based questionnaire to assess parental awareness. The questionnaire was distributed to parents of children attending paediatric orthopaedic clinics in a single Teaching Hospital Trust over a period of four months. Results: 220 parents responded to the questionnaire. 85% of respondents believed vitamin D to be important for the health of a child. 65% said they knew what vitamin D was. 40% of all parents asked were unable to write a brief statement of their basic understanding surrounding vitamin D. 17% give their children vitamin D supplementation. 2% of the respondents' children have been told they are vitamin D deficient. The participants were asked what they believed to be good dietary sources of vitamin D. 64% of respondents could identify oily fish or eggs. However, 46% believed dairy products to be a good dietary source of vitamin D. The questionnaire asked respondents whether GPs have provided education or advice about the importance of maintaining adequate vitamin D levels in children, only 9% of parents said that they had received information from their child's GP. 59% of respondents to the questionnaire wanted more information about vitamin D and vitamin D deficiency. This information was sent to each of those respondents as a short leaflet. Conclusion: Parental awareness of vitamin D and deficiency is poor. There is a need for increased levels of parental education to ensure children have a better chance of maintaining adequate vitamin D levels.